2018
DOI: 10.1096/fj.201801285r
|View full text |Cite
|
Sign up to set email alerts
|

IL‐13 signaling through IL‐13 receptor α2 mediates airway epithelial wound repair

Abstract: Asthma is an airway inflammatory disease characterized by epithelial barrier dysfunction and airway remodeling. Interleukin‐13 (IL‐13) is a pleiotropic cytokine shown to contribute to features of airway remodeling. We have previously demonstrated that IL‐13 is an important mediator of normal airway epithelial repair and health. The role of IL‐13 signaling via its receptor subunits (IL‐13Rα1/IL‐4Rα and IL‐13Rα2) in airway epithelial repair and restoration of intact barrier function is not well understood and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…2 a). This is based on loss of function approach suggesting that in the absence of IL-4Rα/IL-13Rα1 heterodimer (receptor subunit for IL-4 and IL-13), IL-13 can only exert its effects on cognitive function by signaling via the only other available receptor subunit, which is IL-13Rα2 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…2 a). This is based on loss of function approach suggesting that in the absence of IL-4Rα/IL-13Rα1 heterodimer (receptor subunit for IL-4 and IL-13), IL-13 can only exert its effects on cognitive function by signaling via the only other available receptor subunit, which is IL-13Rα2 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a complicated airway inflammatory disease characterized by airway remodelling resulting from epithelial damage, glandular hyperplasia and subepithelial fibrosis . Current epidemiological results show that asthma has affected approximately 300 million individuals worldwide .…”
Section: Introductionmentioning
confidence: 99%
“…IL-13 is required to the development of asthma [20] and induces different biological effects in airway in ammatory and structural cells [21]. More importantly, IL-13 is central to the pathogenesis of airway remodeling of asthma by acting on airway epithelial cells [22,23], broblasts [6], ASMCs [21] and induces goblet cell metaplasia, mucus hypersecretion, ASMCs proliferation and migration, broblasts proliferation, airway hyperreactivity and elevated IgE levels [21], all features of airway remodeling. We have previously shown that IL-13 upregulated Orai1 and STIM1 expression and SOCE in cultured ASMCs [8], consistent with the results in the current study that IL-13 dose-dependently increased the mRNA and protein expression of Orai1 in hBSMCs.…”
Section: Discussionmentioning
confidence: 99%